Use of CRIB II (Clinical Risk Index for Babies) Score for Prediction of Mortality in Premature Babies Admitted in A Tertiary Care Hospital (Dhaka Shishu (Children) Hospital Journal, 2024)
Background: Neonatal mortality accounts for about two-thirds of all infant deaths. The major causes of neonatal mortality are prematurity/low birth weight (LBW) and congenital anomalies. Application of severity scores in this condition may be useful for prognostication. Clinical risk index for babies (CRIB II) score is a tool to predict initial risk of mortality amongst preterm low birth weight babies, the utility of which is scarce in many developing countries. Objective: To assess the ability of the CRIB II score to predict mortality of preterm babies before hospital discharge. Methods: This was a cross-sectional study, carried out at Department of Neonatal Medicine, Dhaka Shishu Hospital from August 2013 to January 2014. Preterm newborns of 28-32 weeks, birth weight between 750-1500 gm and admitted within 12 hours of age were purposively included in this study and babies having lethal congenital malformations were excluded. The demographic data including age, sex, birth weight, temperature and after doing arterial blood gas analysis base excess were recorded in the questionnaire. CRIB II score was determined and recorded. Receiver operating characteristic (ROC) analysis and the area under the receiver operating characteristic curve (AUC) was calculated for the predictive performance of CRIB II score. Results: One hundred and thirty two neonates met the inclusion criteria. Approximately half (51.5%) neonates belonged to age £6 hours and more than half (56.1%) neonates were male. The mean gestational age was 29.7±1.6 week with 60.6% were of £30 weeks. The CRIB II score was ranged from 2 to 15 with mean 8.7±3.3. Among the enrolled neonates mortality was 37.1%. Mortality was significantly (p